Scd-1 deficiency promotes the differentiation of CD8+ T effector - Lin, Yiwei; Li, Xushuo; Shan, Haojie; Gao, Jie; Yang, Yanying; Jiang, Linlan; Sun, Lu; Chen, Yuwen; Liu, Fangming; Yu, Xiaowei (Frontiers in Cellular and Infection Microbiology, 2024)
The impact of various fatty acid types on adaptive immunity remains uncertain, and their roles remain unelucidated. In this study, we showed that the enzyme stearoyl-CoA desaturase-1 (Scd-1) and its resulting compound, oleic acid (OA), have a substantial impact on the transformation of CD8 + naïve T cells into effector T cells.Inactivation of Scd-1 triggers the specialization of CD8 + T cells into the Teff subset, enhancing the effector function and mitochondrial metabolism of Teff cells, and OA can partially counteract this. In the LCMV infection model, Scd-1 deficiency enhances resistance to viral infection. In animal models of endotoxemia, OA alleviated symptoms, reduced inflammation, and affected the differentiation and effector function of CD8 + T cells.